Being a successful interpreter adding value and delivering excellence - Downie, Jonathan (Routledge, 2016)
Being a Successful Interpreter is a practical and thorough guide to the business and personal aspects of interpreting. Written in an engaging and user-friendly manner, it is ideal for professional interpreters practising in conference, medical, court, business and public service settings, as well as for students and recent graduates of interpreting studies